2013
DOI: 10.1152/japplphysiol.00239.2012
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with brain natriuretic peptide reduces skeletal muscle mitochondrial dysfunction and oxidative stress after ischemia-reperfusion

Abstract: Brain natriuretic peptide (BNP) reduces the extent of myocardial infarction. We aimed to determine whether BNP may reduce skeletal muscle mitochondrial dysfunctions and oxidative stress through mitochondrial K(ATP) (mK(ATP)) channel opening after ischemia-reperfusion (IR). Wistar rats were assigned to four groups: sham, 3-h leg ischemia followed by 2-h reperfusion (IR), pretreatment with BNP, and pretreatment with 5-hydroxydecanoic acid, an mK(ATP) channel blocker, before BNP. Mitochondrial respiratory chain c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
2
26
0
1
Order By: Relevance
“…Besides its role in the immune response, there are various ways by which CD26 may participate in controlling the response to hyperoxia. First, a diminished degradation of CD26 substrate peptides with antioxidant capacity promotes their activity, which represents an obvious advantage in hyperoxic conditions (5,32,44,49,60). For example, a decreased degradation of the vasoactive intestinal peptide is consistent with the observation that its serum level increases following production of reactive oxygen species, which constitutes an adaptive response because the peptide has per se antioxidative capacities via its capacity to scavenge singlet oxygen and to reduce hydroxyl radical production (5,32,41,44).…”
Section: Discussionmentioning
confidence: 83%
“…Besides its role in the immune response, there are various ways by which CD26 may participate in controlling the response to hyperoxia. First, a diminished degradation of CD26 substrate peptides with antioxidant capacity promotes their activity, which represents an obvious advantage in hyperoxic conditions (5,32,44,49,60). For example, a decreased degradation of the vasoactive intestinal peptide is consistent with the observation that its serum level increases following production of reactive oxygen species, which constitutes an adaptive response because the peptide has per se antioxidative capacities via its capacity to scavenge singlet oxygen and to reduce hydroxyl radical production (5,32,41,44).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, according to the results of a previous study, 'Baihui acupoint (GV20)'-stimulation with a density-sparse wave of 2/15 Hz and an intensity of 1 mA for 30 min/day over five consecutive days was reported to induce cerebral I/R tolerance (32). Evidence has suggested that I/R disturbs energy metabolism, increases oxidative stress and triggers apoptotic cell death (33). Previous studies have reported that EA pretreatment exerted neuroprotective effects against I/R injury via regulation of oxidative stress, maintenance of blood-brain barrier integrity and inhibition of apoptosis via various receptors (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…They also have beneficial effects in T2DM with PAD because natriuretic peptides can promote angiogenesis, modify the function of vascular endothelial cells, reduce cardiac load, and improve blood supply to the legs owing to their diuretic and vasodilatory effects [35-37]. In Wistar rats, pretreatment with BNP can attenuate the excessive production of radical oxygen species [38]. Various studies have indicated that BNP has aprotective role in vascular disease, butour data support the notion that higher BNP levels predispose to PAD development in T2DM.…”
Section: Discussionmentioning
confidence: 99%